2014
DOI: 10.1371/journal.pone.0105438
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effects of Plant Genotypic and Species Diversity on Anti-Herbivore Defenses in a Tropical Tree Species

Abstract: Despite increasing evidence that plant intra- and inter-specific diversity increases primary productivity, and that such effect may in turn cascade up to influence herbivores, there is little information about plant diversity effects on plant anti-herbivore defenses, the relative importance of different sources of plant diversity, and the mechanisms for such effects. For example, increased plant growth at high diversity may lead to reduced investment in defenses via growth-defense trade-offs. Alternatively, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
97
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 65 publications
(108 citation statements)
references
References 58 publications
4
97
3
Order By: Relevance
“…In particular, the likelihood of associational resistance increases with the functional dissimilarity of associated trees in mixed forests (Castagneyrol et al 2014a). This would explain why there is weak evidence for better resistance of pure stands composed of several genotypes of the same species compared to single-genotype monocultures (Moreira et al 2014;Barton et al 2015).…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 99%
“…In particular, the likelihood of associational resistance increases with the functional dissimilarity of associated trees in mixed forests (Castagneyrol et al 2014a). This would explain why there is weak evidence for better resistance of pure stands composed of several genotypes of the same species compared to single-genotype monocultures (Moreira et al 2014;Barton et al 2015).…”
Section: Effects Of Forest Tree Diversity On Pest Regulation Of Nativmentioning
confidence: 99%
“…Alternatively, effects of plant diversity arising via increased plant growth could be controlled statistically by testing for diversity effects on herbivores with and without plant biomass as a covariate [12,40] or analysing effects on insect abundance versus density (number of insects per unit of plant biomass). If diversity effects are mediated by plant biomass then significant effects on herbivores should disappear once biomass is accounted for [41 ]. Greater plant growth rates at high diversity may also lead to reduced investment in plant defences via growth-defence trade-offs or, alternatively, to increased levels of plant defences via increased herbivore loads and damage (i.e.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%
“…induced defences). In this sense, Moreira et al [41 ] found that plant species and genotypic diversity had positive effects on mahogany chemical defences, but these positive diversity effects on defences were not mediated by either growth-defence trade-offs or changes in herbivore damage. Further studies should thus investigate plant diversity effects on anti-herbivore defences at a finer/more mechanistic level.…”
Section: Effects Of Plant Diversity On Plant-insect Herbivore and Hermentioning
confidence: 99%
“…Plant diversity may also influence plant traits such as chemical or physical defences against herbivores (Mraja et al, 2011;Moreira et al, 2014Moreira et al, , 2017Kostenko et al, 2017), and these effects may contribute to explain effects of diversity on plant-herbivore interactions. Diversity effects on plant traits may be due to changes in abiotic conditions (e.g.…”
Section: Introductionmentioning
confidence: 99%